Evidence of novel pathogenic pathways for the formation of antigastric autoantibodies in Helicobacter pylori gastritis. Issue 3 (March 1998) - Faller, G; Steininger, H; Appelmelk, B; Kirchner, T
Abstract : Autoantibodies against gastric epithelial cells are detectable in up to 50% of patients with chronic, active Helicobacter pylori gastritis. Presence of autoantibodies against canalicular structures within human parietal cells (anticanalicular autoantibodies) correlate with gastric mucosa atrophy. It has been suggested, that molecular mimicry between H pylori and the host on the level of Lewis X and Lewis Y blood group antigens leads to these autoantibodies. This study aimed at analysing whether antigastric antibodies can be absorbed to Lewis X or Y positive H pylori strains. Sera from 14 H pylori infected patients with anticanalicular autoantibodies were effectively absorbed to H pylori. Immunohistochemical studies of the absorbed sera showed no decrease of antigastric autoreactivity. Pathogenic mechanisms other than molecular mimicry lead to the formation of antigastric autoantibodies, and epitopes other than Lewis antigens are the autoimmune targets.